(untitled) (An Nawawi, 2025)
The rapid development of digital financial innovation has transformed the structure and practices of the Islamic financial system, raising questions regarding its compliance with Islamic legal principles. This study aims to analyze the development of digital Islamic financial innovation from the perspective of fiqh muamalah and maqāṣid al-syarī‘ah. Using a qualitative approach with a normative-conceptual method, this research examines classical and contemporary fiqh literature, regulatory frameworks, and scholarly views related to Islamic digital finance. The results show that digital financial innovation in the Islamic economic system is fundamentally permissible, in line with the fiqh maxim al-aṣl fī al-mu‘āmalāt al-ibāḥah illā an yadulla dalīlun ‘alā al-taḥrīm, as long as it does not contradict sharia principles such as the prohibition of riba, gharar, and maysir. Furthermore, the maqāṣid al-syarī‘ah approach demonstrates that digital Islamic financial innovation contributes to the realization of public welfare (maṣlaḥah), particularly in terms of efficiency, financial inclusion, and transparency. Therefore, the integration of fiqh muamalah and maqāṣid al-syarī‘ah provides a comprehensive framework for assessing and developing sustainable digital Islamic financial innovations.